Disturbance and disease - Lambin, E.F.; Anugwom, E.; Prist, P.R.; Agha, S.; White, S.; Grace, Delia; Khan, S.A.; Fèvre, Eric M.; Gottdenker, N.; Murray, K. (Elsevier, 2025)
The world has witnessed an alarming rise in the emergence of infectious diseases, posing profound challenges to public health, ecological balance, and global well-being. Displacement of people and the destabilization of ecosystems create conditions that significantly amplify the risk of disease outbreaks. In this Voices, we ask: how has anthropogenic environmental disturbance impacted the likelihood of disease outbreaks?